2015
DOI: 10.1248/cpb.c15-00386
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of Novel Carbocyclic Oxetanocin A (COA-Cl) Derivatives as Potential Tube Formation Agents

Abstract: Six novel carbocyclic oxetanocin A analogs (2-chloro-C.OXT-A; COA-Cl) with various hydroxymethylated or spiro-conjugated cyclobutane rings at the N 9 -position of the 2-chloropurine moiety were synthesized and evaluated using human umbilical vein endothelial cells. All prepared compounds (2a-f) showed good to moderate activity with angiogenic potency. Among these compounds, 100 µM cistrans-2′,3′-bis(hydroxymethyl)cyclobutyl derivative (2b), trans-3′-hydroxymethylcyclobutyl analog (2d), and 3′,3′-bis(hydroxymet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…[6][7][8]15) Secondary alcohols 3a-d were treated with 2,6-dichloropurine and underwent the Mitsunobu reaction [15][16][17][18] in the presence of PPh 3 and diisopropyl azodicarboxylate (DIAD) to give 9-cyclopropylmethyl-2,6-dichloropurine congeners 4a-d in 29-49% yield. Then, 4c was subsequently treated with methanolic ammonia to obtain the desired product 2c in 67% yield.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8]15) Secondary alcohols 3a-d were treated with 2,6-dichloropurine and underwent the Mitsunobu reaction [15][16][17][18] in the presence of PPh 3 and diisopropyl azodicarboxylate (DIAD) to give 9-cyclopropylmethyl-2,6-dichloropurine congeners 4a-d in 29-49% yield. Then, 4c was subsequently treated with methanolic ammonia to obtain the desired product 2c in 67% yield.…”
Section: Resultsmentioning
confidence: 99%
“…4) In a single exceptional case, a COA-Cl analog (1e), regioisomer of the two hydroxymethyl groups at the cyclobutane ring of 1a, exhibited angiogenic activity that was comparable to that of COA-Cl 1a. 7) Collectively, these studies indicated that the structure of not only the cyclobutane ring moiety but also the 2-substituted purine skeleton in COA-Cl 1a is essential for angiogenic activity.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…COA-Cl (6-amino-2-chloro-9-[trans-trans-2,3-bis(hydroxymethyl)cyclobutyl]purine) is a recently synthesized novel nucleic acid analog, which has adenosine-like structure [6]. There are some reports showing beneficial effects of COA-Cl in in vitro and in vivo experiments.…”
Section: Introductionmentioning
confidence: 99%